Bioaugmentation with Ruminiclostridium thermocellum M3 to enhance thermophilic hydrogen production from agricultural solid waste. Issue 6 (12th February 2021) - Sheng, Tao; Meng, Qingbin; Wen, Xuechen; Sun, Caiyu; Yang, Lisha; Li, Lixin
Abstract: BACKGROUND: High‐efficiency saccharification technology is one of the bottlenecks of cellulosic bio‐hydrogen production. Cellulosic feedstocks saccharification currently performed by commercial cellulase, which is composed of different fungal cellulase. Compared with fungi, thermocellulosic bacteria represented by Ruminiclostridium thermocellum have a complete cellulase system, and a higher cellulase catalytic efficiency than fungi; however, R. thermocellum is susceptible to feedback inhibition by cellobiose, which limits the application of R. thermocellum on cellulosic bio‐hydrogen production. In this study, a strain named R. thermocellum M3, which is not subject to feedback inhibition by cellobiose, was used in the bio‐hydrogen production of cellulosic agricultural waste feedstocks to explore the feasibility of bacterial saccharification of cellulosic substrates for biological hydrogen production. RESULTS: Results of batch tests indicate that the combination of domestic sewage sludge and strain M3 promoted the hydrogen production for different lignin content feedstocks (rice straw: from 0.66 to 6.42 mmol H2 /g substrate; corn cob: from 0.61 to 5.55 mmol H2 /g substrate; pine wood waste: from 0.58 to 5.32 mmol H2 /g substrate), which were competitive with the combination of domestic sewage sludge and Trichoderma viride cellulase. Specific activity analysis indicates that compared with the addition of T. viride cellulase, the addition of strain M3 completed the cellulase system in sludge. CONCLUSION: Thermo‐anaerobic bacteria R. thermocellum M3 enhanced the hydrogen production of the consolidated bioprocessing (CBP) of raw lignocellulosic agricultural wastes and, more importantly, provided a promising solution for the CBP strategy in the industrial application of lignocellulose bioconversion. © 2021 Society of Chemical Industry